Polymer-based composite repair system for severely corroded circumferential welds in steel pipes. (November 2017) - Watanabe Junior, M.M.; Reis, J.M.L.; da Costa Mattos, H.S.
Abstract: In offshore installations, the use of piping is crucial for transporting different kinds of fluids. In this kind of environment, corrosion is one of the major damage mechanisms of the metallic pipelines, due to aggressive fluid and atmosphere. Duplex and Super duplex stainless steel pipes are increasingly being used in offshore platforms due to the excellent material's resistance to corrosion combined with good mechanical properties. However, the welding process is not simple and a high susceptibility to corrosion may occur if some parameters are not very well controlled. Severe corrosion damage in some weld beads eventually impairs the serviceability, mainly through-wall defects that cause leaks in the pipelines. The main motivation is the duplex and super duplex stainless steel pipes that are increasingly being used in offshore platforms due to the excellent material's resistance to corrosion combined with good mechanical properties. However, the welding process is not simple and a high susceptibility to corrosion may occur if some parameters are not very well controlled. Severe corrosion damage in some weld beads eventually impairs the serviceability, mainly through-wall defects that cause leaks in the pipelines. Examples concerning the use of composite repair systems in different damage situations (artificial defects aim at reproducing localized corrosion damage defects found in real welded joints) show the possibility of effective use of the proposed alternative procedure as a reliable tool for lifetime extension and to reduce the pipeline downtime. This methodology is conceived to adequately repair weld joints presenting damage up to 80% of the wall thickness and through-wall defect up to 50% of the perimeter of the pipe. Highlights: Corrosion damage in weld beads may impair the serviceability of super duplex pipes. A polymer-based composite repair system for severely corroded pipes is considered. The repair of trough-wall corrosion damage in circumferential welds is investigated. The focus is to assure that the pipe won't leak after the repair. This repair system is a reliable tool for lifetime extension and to reduce downtime.